WOMEN'S FOLK DANCING IN "BOOK COLLECTION FOR FOLKLOREAND ETHNOGRAPHY" IN TEN VOLUMES - Tulishova, Gergana (E-Journal VFU, 2024)
This article focuses on the study of women's folk dancing in publicationsfrom volumes I to X of the Book Collection for Folklore and Ethnography. The texts show thestate of traditional folk culture in the period 1889-1894. The contexts and communicativesituations of which dancing was a part are examined. The parameters used to describe danceactivity in this early stage of traditional culture research are outlined. The stage at which folkdance comes into the sight of scholars from different scientific fields. Attention is drawn tothe research line that follows the development of the collection.
Keywords: Book Collection for Folklore and Ethnography; women's folk dancing; context; discourse